PENGARUH PENERAPAN AKUNTANSI PERTANGGUNGJAWABAN, KOMITMEN ORGANISASI DAN KOMPETENSI TERHADAP KINERJA MANAJERIAL - Anindya Nur Arifah; Lisa Nuriyatul Azizah; Dewi Indriasih (LPPM Politeknik Pratama, 2022)
Performance is a measure that can be used to emphasize behaviors and attitudes that should not occur and to instill desirable behavior. Managerial performance is a very important matter to measure the success of a company. Managerial performance adds value to work done well. Companies often take action and apply to managerial performance to ease their work. The purpose of this study is to strengthen evidence of the influence of the application of responsibility accounting, organizational commitment, and competence on managerial performance. The data used in this study are primary data that takes samples of several managerial performances at the company. The results of this study indicate that there is an influence on managerial performance. This research uses purposive sampling method. The data used are quantitative with the results of questionnaire data and using qualitative data according to a list of respondents' statements on the questionnaire.